PENGEMBANGAN MODUL BERGAMBAR YANG DILENGKAPI PETA KONSEP PADA MATERI SISTEM REGULASI UNTUK SMA - Yenti, Fitri - (Pendidikan Biologi, 2014)
The use of module exactly has been implemented in SMAN 6 Padang. But the module which is used canât be used yet to help student in understanding the lesson especially Biology in regulation system of human because in module thereâs still incomplete material to be taught. Some lacks of module which is used like including words that wrong written including concept written, uninteresting module look, unavailable concept description in detail, and uncolorful picture. The aim of this research is to produce picture module which is completed by map concept in regulation system for class XI in Senior High School. The type of this research is developing the research by using model 4-D developing which is modified from Thiagarajan and Semmel (1974 in Trianto, 2012:94) . In this research including 3 level, they are define, design, and develop. This research has been done and tried in August 28 2014 to two teachers and 30 students in class XII in SMAN 6 Padang. The result of this research is to produce the picture module which is completed with concept map in regulation system material that is valid with the score of validity is 88,54% and valued by construction requirement, and technical . Then the nodule which is produced also include in simple criteria with the value 84,54%, and valued by student interest as variable and module look, process of use, concept and material understanding , time and evaluation. It can be concluded that picture module which is completed with map concept in regulation system material that is produced has fulfilled valid criteria and simple.